Culture conditions for the production of thermostable lipase by thermomyces lanuginosus - Sreelatha, B.; Vankudoth, Koteswara Rao; Kumar, R. Ranjith; Girisham, Sivadevuni; Reddy, S. M. (Journal of Basic and Applied Sciences, 2016)
In the present investigation lipase production by three strains of thermophilic Thermomyces lanuginosus (GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14) was carried out in submerged fermentation process. Olive oil and triacetin (0.1%) were added to the basal medium, which stimulated the lipase production. The maximum lipase was produced by GSLMBKU-10 and GSLMBKU-13 in yeast extract starch medium supplemented with triacetin (0.1%). The optimum pH was recorded at 6.0, 6.5 and 7.0 by GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14 respectively. T. lanuginosus GSLMBKU-10 strains failed to produce lipase at pH 8.0. The optimum temperature for lipase production was observed at 45 °C by GSLMBKU-14 and GSLMBKU-10, while that for GSLMBKU-13 was at 50 °C. The marginal temperature ranged from 45 °C to 50 °C for both lipase production and vegetative growth by the three strains of T. lanuginosus under study. In conclusion, the GSLMBKU-13 strain was comparatively superior in the production of lipase than the other two strains under investigation.

Isolation and molecular characterization of thermophilic coprophilous fungus malbranchea cinnamomea GSMBKU from goat dung - Ajmera, Shanthipriya; Rao, V. Koteswara; Ranipadmini, V.; Merugu, Ramchander; Girisham, Sivadevuni (Journal of Pure and Applied Microbiology, 2019)
Thermophilic fungi, found in the varied habitats are valuable sources for potential enzymes and other biochemical metabolites throwing challenges to the mycologists. A study of such fungi will not only enables the biochemists, microbiologists, and the biotechnologists to understand the basic molecular process but also search for novel genes, gene products and reactions. In this study, Malbranchea cinnamomea was isolated from goat dung and characterized based on its morphological and physiological characters, and later confirmed molecularly.